Etiopathogenesis of vaginal discharge among married women in reproductive age group residing in rural area of Bhojipura District, Western Uttar Pradesh - Agrawal, Monica; Nigam, Nitu; Goel, Ruchica; Goel, J. K.; Shukla, Mukesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vaginitis is one of common medical problem in women that often results in frequent medical consultations. Aim was to study the clinico-epidemiological profile and etiopathogenesis of various causes of vaginal discharge among females in age group 18-45 years residing in rural area of Bhojipura district. Methods: This Hospital based cross sectional study was conducted over a period of one year (March 2011 to February 2012) among 150 females aged 18-45 years presenting with the complaint of vaginal discharge. Information on sociodemographic data was obtained with the aid of questionnaires. Samples were obtained with two dry cotton-wool tipped swabs from vaginal fornices and were sending to department of microbiology. Results: The prevalence rate of vaginal discharge was found to be 24.6% among females in reproductive age group attending the outpatient department from rural background. Out of 150 patients who were enrolled for study 86 (57.30%) were diagnosed with non-infective discharge while 64 (42.60%) patients with infective discharge. Bacterial vaginosis was detected in 25 (39.1%), Candida albicans was detected in 23 (35.9%), T. vaginalis in 4 (6.3%) and mixed infections were found in 12 (18.7%). According to vagina flora morphology 85 (56.6%) had normal morphology, 30 (20%) had shift from normal flora and 35 (23.3%) had definitive bacterial vaginosis. About 20.5% females with Candida based etiology were diabetic. Conclusions: Some common reproductive tract infections can be diagnosed and managed at primary level health facilities. This promotes community awareness through behavior change communication which includes safer sex practices, awareness of HIV and appropriate and timely health care seeking behavior.